2017
DOI: 10.1002/jssc.201700073
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of arginine-modified reduced graphene oxide composite filled in an on-line solid-phase extraction disk and its application in the analysis of heterocyclic aromatic amines

Abstract: An arginine-modified reduced graphene oxide composite was prepared in an on-line solid-phase extraction disk and coupled to high-performance liquid chromatography for the re-enrichment of heterocyclic aromatic amines. The synthetic composite presented an excellent adsorption capability because of the ultrahigh active surface area of graphene and the abundant alkaline groups of arginine. The adsorption capacity of it was 52.7 mg 2-amino-3-methyl-imidazo[4,5-f]-quinoline per gram, nearly twice that of threonine-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 43 publications
0
12
0
Order By: Relevance
“…HPLC is the most common technique applied for the analysis of HAAs because it does not require derivatization process and requires minimal preparation. Over the last two decades, a number of LC‐based studies (summarized in Table ) by coupling with different kinds of detectors have been reported for the analysis of HAAs in foodstuffs including LC‐DAD (Agudelo Mesa et al., ; Cai et al., ; Cárdenes et al., ; Janoszka, Blaszczyk, Damasiewicz‐Bodzek, & Sajewicz, ; Melo et al., ; Özdestan et al., ; Tan et al., ), LC‐ECD (Bermudo, Ruiz‐Calero, Puignou, & Galceran, ; Martin‐Calero et al., ), LC‐FLD (Basheer, ; Jautz et al., ; Martín‐Calero et al., ; Martin‐Calero, Tejral, Ayala, Gonzalez, & Afonso, ; Ristic, Cichna, & Sontag, ), LC‐UVD (Aeenehvand et al., ; Yao et al., ; Zhang et al., ; Zhang et al., ), LC‐PDA (Vichapong et al., ; Vichapong, Srijaranai, Santaladchaiyakit, Kanchanamayoon, & Burakham, ), LC‐amperometric detector (Maria Bueno, Angel Marin, Maria Contento, & Rios, ), and HPLC‐coulometric electrode array detection (Gerbl, Cichna, Zsivkovits, Knasmüller, & Sontag, ).…”
Section: Instrumental Analytical Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…HPLC is the most common technique applied for the analysis of HAAs because it does not require derivatization process and requires minimal preparation. Over the last two decades, a number of LC‐based studies (summarized in Table ) by coupling with different kinds of detectors have been reported for the analysis of HAAs in foodstuffs including LC‐DAD (Agudelo Mesa et al., ; Cai et al., ; Cárdenes et al., ; Janoszka, Blaszczyk, Damasiewicz‐Bodzek, & Sajewicz, ; Melo et al., ; Özdestan et al., ; Tan et al., ), LC‐ECD (Bermudo, Ruiz‐Calero, Puignou, & Galceran, ; Martin‐Calero et al., ), LC‐FLD (Basheer, ; Jautz et al., ; Martín‐Calero et al., ; Martin‐Calero, Tejral, Ayala, Gonzalez, & Afonso, ; Ristic, Cichna, & Sontag, ), LC‐UVD (Aeenehvand et al., ; Yao et al., ; Zhang et al., ; Zhang et al., ), LC‐PDA (Vichapong et al., ; Vichapong, Srijaranai, Santaladchaiyakit, Kanchanamayoon, & Burakham, ), LC‐amperometric detector (Maria Bueno, Angel Marin, Maria Contento, & Rios, ), and HPLC‐coulometric electrode array detection (Gerbl, Cichna, Zsivkovits, Knasmüller, & Sontag, ).…”
Section: Instrumental Analytical Methodsmentioning
confidence: 99%
“…Another recent study conducted by Cai et al. () reported an online solid‐phase extraction disk coupled to HPLC‐DAD method for the detection of HAAs in beef jerky (Cai et al., ). HPLC‐PDA has also been utilized for the determination of HAAs (Vichapong et al., ), and the proposed method has successfully detected the HAAs in smoked sausages with LODs ranging between 1 and 3 µg/kg.…”
Section: Instrumental Analytical Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although lacking evidence to support the hypothesis that excessive uptake of HAs could directly cause cancer, the International Agency for Research on Cancer has already decided a limitation of HAs . HAs have been discovered in different matrices . Most of the researchers have isolated and identified them in food samples and related substances.…”
Section: Introductionmentioning
confidence: 99%